Development of a Digital Tolerance Module as a Supplement to Basic BIPA Learning to Improve Intercultural Communication Competence - Dewi Lailatul Maghfiro; Prima Vidya Asteria (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to develop a digital tolerance module as a supplement to elementary-level BIPA learning in order to improve intercultural communication skills. The research used the Research and Development (R&D) method adapted from Borg and Gall, which includes 1) potential and problems, 2) data collection, 3) product design, 4) product validation, 5) product revision, 6) testing, and 7) final revision. The research subjects were a small heterogeneous class of UNESA Basic Level BIPA learners from various countries. Data collection techniques were obtained through interviews, document studies, and validation questionnaires regarding materials and media. The research instruments included interview guidelines, document studies, and expert validation questionnaires on materials and media. The research data analysis used qualitative and quantitative methods (mixed methods). The results showed that the development of this digital module produced a supplementary product that integrated tolerance values into Basic BIPA language materials through interactive multimedia features. The development procedure successfully transformed learners’ needs for sociocultural material into a product design that was validated by experts. Based on the validation test results, the digital tolerance module scored 85% in the “Highly Valid” category in terms of material and media. These findings indicate that the digital tolerance module is suitable for use as a supplement to Basic BIPA learning to support the strengthening of intercultural communication competencies.